Analise de desempenho de observadores de estado robustos na localizacao de falhas - de Melo, Gilberto Pechoto [UNESP]; Pederiva, Robson [UNESP] (My University, 2000)
The state observers can reconstruct and monitor unmeasurable states. A new concept of fault detection and isolation using state observers is presented. The method selects the parameters from components that may fail during the process and constructs optimized robust observers. To isolate component failures via robust observation, a bank of detection observers is organized, in which each observer is only sensitive to one specified component failure while robust to all other component failures. This paper analyzes the performance of transient and steady-state behavior of the state observer.
Performance analysis of robust state observers in fault location
Keywords: Identification (control systems); Optimization; Robustness (control systems); State estimation; Transients; Robust state observers; Electric fault location